DIGITAL FORENSICS ON ANDROID DEVICE (Balkan Journal of Applied Mathematics and Informatics, 2024)
The science of digital forensics is an ever-changing and complex field which demands continuous advancements and development. It involves examining and extracting data from electronic devices which can consequently be used as digital evidence in the investigation of potential criminal activities.The forensic experts work tirelessly on finding new and improved tools which can make the research in the field more effective and the practical work of the examiners more productive. The processes and procedures are also constantly updated to follow the technological advances, in order to keep up with the trends lead by the manufacturers of electronic devices.The following research paper provides detailed description of the process of examination and extraction of data from mobile phones with android operating system. The detailed description explains the standardized procedures in stages, categorized in logical and chronological order to depict the work tasks of a digital forensic examiner.In addition to the theoretical explanation, this paper also offers practical examples of digital forensic examination. This practical examination was conducted to supports the key points of the elaborated research. Key words: digital forensics, mobile phone, android operating system
Keywords: digital forensics, mobile phone, android operating system